2017
DOI: 10.1002/adfm.201606694
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Increased Raman Enhancement on MoX2 (X = S, Se) Monolayers upon Phase Transition

Abstract: 2D transition metal dichalcogenide (TMD) materials have been recognized as active platforms for surface‐enhanced Raman spectroscopy (SERS). Here, the effect of crystal structure (phase) transition is shown, which leads to altered electronic structures of TMD materials, on the Raman enhancement. Using thermally evaporated copper phthalocyanine, solution soaked rhodamine 6G, and crystal violet as typical probe molecules, it is found that a phase transition from 2H‐ to 1T‐phase can significantly increase the Rama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
169
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(173 citation statements)
references
References 60 publications
(67 reference statements)
2
169
2
Order By: Relevance
“…Two‐dimensional layered transition metal dichalcogenides (TMDs) of the MX 2 molecular form (M = Mo, W, Bb, Ta, Ti, Re; X = S, Se, Te) have attracted a significant interest recently because of their unique photonic and optoelectronic properties . Very recently, several members of the TMDs family, especially MoS 2 with a visible‐range bandgap (1.9 eV and 1.2–1.4 eV for single‐ and multilayer MoS 2 ) approximately, have been shown to be applicable for SERS . Qiu et al synthesized MoS 2 on flat and Si‐pyramids substrate by thermally decomposing the precursor (NH 4 ) 2 MoS 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two‐dimensional layered transition metal dichalcogenides (TMDs) of the MX 2 molecular form (M = Mo, W, Bb, Ta, Ti, Re; X = S, Se, Te) have attracted a significant interest recently because of their unique photonic and optoelectronic properties . Very recently, several members of the TMDs family, especially MoS 2 with a visible‐range bandgap (1.9 eV and 1.2–1.4 eV for single‐ and multilayer MoS 2 ) approximately, have been shown to be applicable for SERS . Qiu et al synthesized MoS 2 on flat and Si‐pyramids substrate by thermally decomposing the precursor (NH 4 ) 2 MoS 4 .…”
Section: Introductionmentioning
confidence: 99%
“…They have also collected the Raman spectra from the Si‐pyramid SERS substrates with sensitivity up to 10 −4 m concentration of adenosine and the authors attributed to low sensitivity to the lack of the surface plasmons on Si‐pyramids substrate. Yin et al synthesized samples of metallic 1T‐MX 2 (with octahedral structure) and the semiconducting 2HMX 2 (with trigonal–prismatic coordination) using a chemical exfoliation method to investigate the Raman enhancement of samples using copper phthalocyanine, Rhodamine 6G (R6G), and crystal violet as probe molecules . They reported that the metallic 1T‐MX 2 has Raman signatures significantly higher for the probe molecules tested compared to semiconducting 2HMX 2 and obtained a SERS sensitivity up to 10 −8 m using R6G molecules and a 532 nm laser as the excitation source.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the FFT image and the atomic image, it can be seen that the applied lateral electric field causes the lattice to “deform”: the lattice vector truea is basically the same size (3.8 Å) and direction, while the length of trueb is shortened (from 3.4 to 2.9 Å) and the angle between the two vectors is increased (Figure g). However, according to the Raman results, the Raman peak shift corresponding to the structural deformation (Figure S10, Supporting Information), such as the 2H phase to the 1T phase transition, does not occur, and hence the lattice distortion is not a real structural change. More over, In consideration of the lateral force signal in the LFM test affected by the electric field, it is inferred that the reduction in the friction energy dissipation is due to the change of the stick‐slip behaviors …”
Section: Resultsmentioning
confidence: 99%
“…Plasmonic resonance was also detected on the boundaries of nanoscale graphene and could even be engineered by the number of defects . Moreover, a distinctive noble metal‐like plasmonic resonance, visible light absorption, and efficient solar H 2 evolution have been elucidated on MoS 2 nanoclusters in the latest research works …”
Section: Introductionmentioning
confidence: 93%